LCMS ANALYSIS OF ROSELLA EXTRACTS (HIBISCUS SABDARIFFA LINN) - Yuditha, Solva; Pakpahan, Evie Lamtiur; Kusparmanto, Lukas (Universitas prof. Dr. Moestopo (Beragama), 2025)
Rosella (Hibiscus sabdariffa Linn) is a traditional medicinal plant with more than 300 species distributed in tropical and subtropical regions. The plant is grown for its fibre as a medicinal ingredient. Rosella has various benefits due to its diverse chemical compounds, such as alkaloids, anthocyanins, flavonoids, tannins, steroids, and sterols. This study discussed the potential of rosella as an anti-inflammatory, antioxidant, antibacterial, antihypertensive, antidiabetic, and anticholesterol. To observe the chemical compound content of rosella flower extract. Methods: LCMS (Liquid Chromatography-Mass Spectrometry) test to see the content of chemical compounds in rosella flower extract. LCMS test showed that rosella flower extract contains flavonoids, tannins, phenolic-quinic acid, phenolic, and alkaloid chemical compounds. Rosella flower extract contains chemical compounds such as flavonoids, tannins, phenolics, quinic acid, and alkaloids, which have antibacterial, antioxidant, anti-inflammatory properties, as well as diuretic, anticholesterol, antidiabetic, and antihypertensive effects. These compounds give rosella great potential as a natural ingredient with various pharmacological applications. Although the results showed that rosella has many pharmacological benefits, further research is still needed to understand the deeper mechanisms and potential clinical use of rosella for the treatment of various diseases, especially in dentistry.